Analysis of the Potential of Private Expenditure on R&D Sector in the Context of the Regional Operational Programme for Opolskie Voivodship 2014–2020 - Malik, Krzysztof; Tkocz, Arkadiusz (Regional Barometer. Analyses & Prognoses, 2017)
Article attempts to assess the possibility of replacing the share of the public sector by private contribution, in the financing of the regional area of research and development. Aim of the research was the determination of the status and the possibility of financing regional R&D from private sources on the example of companies from opolskie region in the perspective of 2020. Contribution to this discussion and analysis was imposed by the European Institutions to meet the requirement of thematic ex-ante conditionality. This condition includes “identification of instruments affecting stimulate private investment in R&D,” as well as “analysis of the regional potential for the possibility of the involvement of private expenditure on R&D.”